Effect of Reproductive Health Education E-Module on Students’ Knowledge and Attitudes Toward Early Marriage Prevention - Annisa Anugrah Damaiyanti; Andi Asmawati Azis; Arifah Novia Arifin (Biology Teaching and Learning, 2026)
Abstract Purpose: This research aims to test the application of the reproductive health education e-module to increase knowledge and change attitudes towards preventing early marriage of MA Al-Ikhlas Nunukan students.Research Methodology: This study used a pre-experimental design (One-Group Pretest-Posttest Design) with a total of 27 students of grade XI MA Al-Ikhlas Nunukan. The research instruments included a knowledge test and an attitude questionnaire given through a pretest and posttest. Data analysis used descriptive analysis and Paired Sample T-test.Results: The descriptive analysis showed that most of the knowledge increased from the very poor category in the pretest to very good in the posttest, and attitudes changed from negative to positive. The inferential test results indicated a significant strengthening of the application of the e-module on knowledge (sig 0.000 < 0.05) and attitudes (sig 0.017 < 0.05) regarding theprevention of early marriage.Conclusions: The application of the reproductive health e-module has a significant positive implication on improving students' knowledge and attitudes toward preventing early marriage.Limitations: This research is a pre-experimental study conducted on a single group of 27 students without a control group.Contributions: This study provides empirical evidence on the effectiveness of digital learning modules (e-modules) in specific regional contexts to address reproductive health education and early marriage prevention.Keywords: Attitude, Early Marriage, E-Module, Knowledge, Reproductive Health